Proceedings of the 49th Annual ACM SIGACT Symposium on Theory of Computing 2017
DOI: 10.1145/3055399.3055483
|View full text |Cite
|
Sign up to set email alerts
|

Non-malleable codes and extractors for small-depth circuits, and affine functions

Abstract: Non-malleable codes were introduced by Dziembowski, Pietrzak and Wichs as an elegant relaxation of error correcting codes, where the motivation is to handle more general forms of tampering while still providing meaningful guarantees. This has led to many elegant constructions and applications in cryptography. However, most works so far only studied tampering in the split-state model where di erent parts of the codeword are tampered independently, and thus do not apply to many other natural classes of tampering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 41 publications
(97 reference statements)
0
39
0
Order By: Relevance
“…In this work, we address the main open problem from [CL17]: we give the first explicit construction of non-malleable codes for small-depth circuits achieving polynomial rate:…”
Section: This Work: Efficient Non-malleable Codes For Small-depth Cirmentioning
confidence: 99%
See 3 more Smart Citations
“…In this work, we address the main open problem from [CL17]: we give the first explicit construction of non-malleable codes for small-depth circuits achieving polynomial rate:…”
Section: This Work: Efficient Non-malleable Codes For Small-depth Cirmentioning
confidence: 99%
“…[ADKO15] showed that a non-malleable code for the simpler G, when concatenated with an (inner) non-malleable reduction (E, D) from F to G, yields a non-malleable code for the more "complex" F. (See Remark 4 for a comparison of our approach to that of [CL17]. )…”
Section: Our Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…We will also use non-malleable codes for the family of affine tampering functions f : {0, 1} n → {0, 1} n , where each output bit of a tampering function can be written as an affine function of the n input bits. Non-malleable codes for this family were explicitly constructed in [3]. Our work.…”
Section: Introductionmentioning
confidence: 99%